2020
DOI: 10.1038/s41598-020-74298-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of multiple sclerosis with vitiligo: a systematic review and meta-analysis

Abstract: Polyautoimmunity implicates that some autoimmune diseases share common etiopathogenesis. Some studies have reported an association between multiple sclerosis (MS) and vitiligo; meanwhile, other studies have failed to confirm this association. We performed a systemic review and meta-analysis to examine the association of MS with vitiligo. We searched the MEDLINE and Embase databases on March 8, 2020 for relevant case–control, cross-sectional, and cohort studies. The Newcastle–Ottawa Scale was used to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…It was reported that HSP70i from melanocytes in accelerating autoimmune vitiligo. Stressed cells secrete HSP70i and in the extracellular environment, HSP70i could activate dendritic cells (DCs) and aid in antigen cross-presentation, resulting in a cytotoxic T cell response to melanocytic antigens (Han Shen et al,2020). The exact role of stress in the pathogenesis of vitiligo and the relationship between stress and the development of various types of vitiligo lesions should be clarified by prospective studies with a clinical and immunoserological focus.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that HSP70i from melanocytes in accelerating autoimmune vitiligo. Stressed cells secrete HSP70i and in the extracellular environment, HSP70i could activate dendritic cells (DCs) and aid in antigen cross-presentation, resulting in a cytotoxic T cell response to melanocytic antigens (Han Shen et al,2020). The exact role of stress in the pathogenesis of vitiligo and the relationship between stress and the development of various types of vitiligo lesions should be clarified by prospective studies with a clinical and immunoserological focus.…”
Section: Discussionmentioning
confidence: 99%
“…Vitiligo is an autoimmune depigmenting dermatosis with multifactorial aetiology and considerable impact on the quality of life. 1,2 The prevalence of vitiligo varies among different populations and ranges from 0.2% to 1.8%. 3 Vitiligo presents with sharply marginated depigmented patches due to a progressive loss of functional melanocytes.…”
Section: Introductionmentioning
confidence: 99%
“…4 Multiple aetiological hypotheses have been proposed, including genetic factors, oxidative stress, protein adhesion defect, and autoimmune reaction. 1 In particular, the autoimmune mechanism is considered the most well established one. 5 Many studies have indicated that in vitiligo patients, a systemic melanocyte destruction happens in the epidermis, hair follicles, mucous membrane, retinal pigment epithelium, leptomeninges, and inner ear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations